A Integration of Social Work in the Public Library: A Comparative Study of San Francisco (USA), Edmonton (Canada), and Melbourne (Australia): https://doi.org/10.60543/ts_iss.vi10.11090 ("Temas Sociais" Journal, 2026)
As public libraries continue to establish themselves as privileged spaces for social inclusion and community intervention, they have assumed an increasingly significant role in responding to the needs of populations experiencing vulnerability. In this context, the present article examines the integration of Social Work in public libraries, drawing on three international experiences: San Francisco (USA), Edmonton (Canada), and Melbourne (Australia). The study is grounded in a qualitative methodology based on literature review, analysis of institutional documents, and consultation of official library webpages, focusing on intervention models, professional profiles, governance frameworks, and community impacts observed during the implementation and consolidation of these programs. The results show that the presence of social workers in libraries contributes to promoting social inclusion, facilitating access to rights, and strengthening mediation with vulnerable populations. It concludes that the public library, as an open community space, constitutes a privileged context for developing interdisciplinary practices that reinforce its social mission.
Keywords: Social Work; Public Libraries; Social Inclusion; Library Social Work